Selumbung Sights: Crafting A Captivating Journey Through Our Official Village Tourism Hub - Ni Wayan Rena Mariani (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Tourist destinations, including the Selumbung tourist village, are starting to improve. But tourist visits to Selumbung village do not show any increase. This is because the Selumbung tourist village has not utilized information technology to promote the beauty of its village. One information technology that can be utilized is the official website. The official website developed by the Destination Management Organization (DMO) is an important tool for branding and promoting a destination. This research aims to analyze what content should be prepared by the Selumbung tourist village so that the official website that will be built meets tourists' needs for information. Developing the content of the Selumbung tourist village website uses 2 approaches. The first approach uses 5 Destination Management System (DMS) components, namely information dimension, communication dimension, transaction dimension, relationship dimension and technical merit dimension. The second approach uses web content analysis, namely information, communication, e-commerce, and additional functional/feature. The content development stages refer to the Extended Model of Internet Commerce Adoption (eMICA) method. Development in the first phase is the Promotion phase which includes detailed information about the Selumbung tourist village. Development in the second phase includes content that can increase website visitor interaction, such as online query forms, online chat, blogs, forums, and satisfaction evaluation features. Development in the third phase includes website reliability and security of user or website visitor data.